Analysis Of The Application Of GMP (Good Manufactoring Practice) In household Scale Pindang Fish Processing : Case Study In Sukabumi City - Maharani, Annisa Nur; Junianto, Junianto (Jurnal Sains dan Teknologi Perikanan, 2025)
This study aims to analyze the application of Good Manufacturing Practice (GMP) in the cob fish pindang processing industry owned by Mr. Wawan in Sukabumi City. The method used is descriptive research through surveys, direct observation at the production site, and interviews with owners to evaluate aspects of sanitation, packaging, and production supervision. The results of the study show that the implementation of GMP in several aspects such as the selection of raw materials and environmental sanitation, has been well implemented. Weaknesses are still found in quality control, sanitation facilities, and product packaging and labeling systems. Packaging that still uses waste paper is at risk of causing contamination. The lack of separation between the areas of raw material receipt, production and storage increases the risk of cross-contamination. Improving GMP standards can be done by improving sanitation systems, using safer packaging, and implementing simple quality controls such as checklists and periodic evaluations. This improvement is expected to improve the quality and safety of pindang products to comply with applicable food standards.